Effect of Elective Cesarean Section on Children's Obesity From Birth to Adolescence: A Systematic Review and Meta-Analysis - Zhang, Shanshan; Qin, Xiaoyun; Li, Peixuan; Huang, Kun (Frontiers in Pediatrics, 2022)
Background Elective cesarean section (ECS) is the most common reason for the increasing cesarean section rate worldwide, and it is reported to be related to adverse short-term and long-term outcomes in both mothers and infants. Findings on the association between ECS and overweight and obesity in children are controversial in recent studies. Therefore, we conducted a systematic review and meta-analysis to examine the effect of ECS on offspring's overweight and obesity. Methods PubMed, Science Direct, Web of Science, CNKI (China National Knowledge Infrastructure), Wanfang Database (in Chinese), and China Biology Medicine disc databases were searched using different combinations of three groups of keywords: “elective cesarean section,” “overweight/obesity,” and “children.” Nine cohort studies and 11 independent risk estimates were finally identified. Results We have observed significant association between ECS and children's obesity, the total pooled risk ratio (RR) being 1.10 (95% CI: 1.01–1.18; I2 = 32.4%). In subgroup analysis, ECS was found to be associated with the occurrence of obesity in preschoolers (RR = 1.12, 95% CI: 1.02–1.22; I2 = 16.8%). Furthermore, it revealed that ECS was related with the high risk of children's obesity where the rate of ECS exceeded 10%. No significant association was observed between ECS and children's overweight, and the RR was 1.12 (95% CI: 0.94–1.30; I2 = 55.6%). Conclusions Overall, it indicated that children born via ECS had an increased risk of later-life obesity. Given the global increase in childhood obesity, our findings would provide evidence-based reference for early life intervention on children's obesity. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021267211, identifier: CRD42021267211.